2021
DOI: 10.1002/1348-9585.12307
|View full text |Cite
|
Sign up to set email alerts
|

Biomatrix of health risk assessment of benzene-exposed workers at Thai gasoline stations

Abstract: Objective This study assessed the health risk of benzene exposure among Thai gasoline station workers through biomarker detection and experience of adverse symptoms. Methods Trans, trans‐muconic acid (tt‐MA) metabolites of benzene were analyzed from spot urine sampled among gasoline station workers after shift work using HPLC‐UV. Air benzene monitoring was done with an active sampler connected to a charcoal sorbent tube, and analyzed by GC‐FID. The health risk was calculated by using the biomatrix of the likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
(28 reference statements)
3
6
0
2
Order By: Relevance
“…A study of Nigerian petrol attendants found that fuel attendants employed for a period of 27-36 months in the petrol station showed a significant increase in SGPT and SGOT activities compared with other petrol attendants that had spent less time in the petrol station [28]. Additional support from our findings is given in that the workers who had SGPT and SGOT values out of the normal range were all from the risk group which was based on the surveillance biomatrix [19].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…A study of Nigerian petrol attendants found that fuel attendants employed for a period of 27-36 months in the petrol station showed a significant increase in SGPT and SGOT activities compared with other petrol attendants that had spent less time in the petrol station [28]. Additional support from our findings is given in that the workers who had SGPT and SGOT values out of the normal range were all from the risk group which was based on the surveillance biomatrix [19].…”
Section: Discussionsupporting
confidence: 70%
“…General characteristics, working characteristics, and adverse symptoms from benzene exposure were collected from 20 workers using a structured questionnaire (general information, working experience, PPE usage, and working behaviour) before blood and urine sampling. The severity of the health effect symptoms experienced in the past 3 years, referenced from the study of Chaiklieng [18,19], was indicated according to 5 levels: no symptoms, mild symptoms, moderate symptoms, severe symptoms, and very severe symptoms.…”
Section: Tt-ma Detection and Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Varias normas de bioseguridad previenen complicaciones en la salud de los trabajadores, siendo este una parte de control de vigilancia obligatoria. (18,19) La mayor parte de solventes orgánicos son considerados contaminantes ambientales, uno de estos; el benceno, posee una elevada volatilidad y composición peligrosa para la salud, la entrada al cuerpo humano se da por absorción cutánea provocando quemaduras en la piel, irritación oftálmica, existe un daño mucho más crónico en personal encargado de despachar gasolina incluyendo efectos adversos a nivel de sistema nervioso central, hepático y renal. (15,20,21) Montano (9) menciona que existe un alto número de estudios epidemiológicos sobre dermatopatías en países europeos.…”
Section: Quemaduras -unclassified
“…Chaiklieng, et al (19) relatan que en mayor proporción los trabajadores que utilizan benceno poseen un mayor riesgo de padecer enfermedades, se menciona que las personas expuestas pueden llegar a prevenir ciertas alteraciones usando un adecuado método de prevención en el cual consiste en un aseo de manos antes de consumir alimentos y una adecuada capacitación.…”
Section: Quemaduras -unclassified